Close Association Between Platelet Biogenesis and Alveolarization of the Developing Lung - Chen, Xueyu; Zhong, Junyan; Han, Dongshan; Yao, Fang; Zhao, Jie; Wagenaar, Gerry. T. M.; Yang, Chuanzhong; Walther, Frans J. (Frontiers in Pediatrics, 2021)
Bronchopulmonary dysplasia (BPD) is a neonatal chronic lung disease characterized by an arrest in alveolar and vascular development secondary to lung immaturity, ventilator-induced lung injury and exposure to hyperoxia in extremely premature infants, leading to a lifelong impairment of lung function. Recent studies indicate that lung plays an important role in platelet biogenesis. However, the dynamic change of platelet production during lung development and BPD pathogenesis remains to be elucidated. We investigated the dynamic change of platelet parameters in extremely premature infants during BPD development, and in newborn rats during their normal development from birth to adulthood. We further studied the effect of hyperoxia exposure on platelet production and concomitant pulmonary maldevelopment in an experimental BPD rat model induced by prolonged exposure to hyperoxia. We detected a physiological increase in platelet count from birth to 36 weeks’ postmenstrual age in extremely premature infants, but platelet counts in extremely premature infants who developed BPD were persistently lower than gestational age-matched controls. In line with clinical findings, exposure to hyperoxia significantly decreased the platelet count in neonatal rats. Lung morphometry analysis demonstrated that platelet counts stabilized with the completion of lung alveolarization in rats. Our findings indicate a close association between platelet biogenesis and alveolarization in the developing lung. This phenomenon might explain the reduced platelet count in extremely premature infants with BPD.